1985
DOI: 10.1111/j.1432-1033.1985.tb08928.x
|View full text |Cite
|
Sign up to set email alerts
|

Human placental neuraminidase

Abstract: Supernatant of homogenized human placenta hardly contains lysosomal neuraminidase activity. It is, however, possible to generate remarkably high activity by concentration of a partially purified glycoprotein fraction. This activity is labile to dilution, but can be stabilized by incubation at 37°C and acid pH. Using β‐galactosidase specific affinity chromatography and immunotitration, we show that the activated and stabilized human lysosomal neuraminidase exists in a complex with β‐galactosidase. Sucrose densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(65 citation statements)
references
References 18 publications
2
63
0
Order By: Relevance
“…Few reports on human lysosomal neuraminidase have been published, because the enzyme has low stability during purification and requires PPCA for the expression of its activity (Verheijen et al 1982(Verheijen et al , 1985(Verheijen et al , 1987Hiraiwa et al 1988;van der Horst et al 1989). Recent cDNA cloning for human lysosomal neuraminidase has revealed that it encodes a 45-kDa protein with three potential N-linked glycosylation sites (Bonten et al 1996;Pshezhetsky et al 1997;Milner et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports on human lysosomal neuraminidase have been published, because the enzyme has low stability during purification and requires PPCA for the expression of its activity (Verheijen et al 1982(Verheijen et al , 1985(Verheijen et al , 1987Hiraiwa et al 1988;van der Horst et al 1989). Recent cDNA cloning for human lysosomal neuraminidase has revealed that it encodes a 45-kDa protein with three potential N-linked glycosylation sites (Bonten et al 1996;Pshezhetsky et al 1997;Milner et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…1. 18) is an acid glycosidase that catalyzes the removal of the terminal sialic acid residues of glycoconjugates (Verheijen et al 1982(Verheijen et al , 1985(Verheijen et al , 1987Hiraiwa et al 1988;van der Horst et al 1989). Mammalian lysosomal neuraminidase is associated with protective protein/cathepsin A (PPCA; EC 3.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Sialidosis results from a defect in a-neuraminidase, which is part of a multienzyme complex within lysosomes that also includes protective protein/cathepsin A (PPCA), and the glycosidases b-galactosidase and N-acetylgalactosamine-6-sulfate sulfatase. 10,11 Association of a-neuraminidase with PPCA, and formation of the multienzyme complex assures the efficient intracellular transport and lysosomal activation of a-neuraminidase. 12,13 Sialidosis is typically classified according to clinical presentation, although this classification scheme does not correlate with specific mutations or the degree of enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the enzyme associates with acid -galactosidase (EC 3.2.1.23) and protective protein/cathepsin A (PPCA, EC 3.4.16.1) to form a multienzyme complex in lysosomes (d'Azzo et al 1982;Verheijen et al 1982Verheijen et al , 1985Hiraiwa et al 1988;van der Horst et al 1989). In paticular, association with PPCA is essential for expression of the sialidase activity (d'Azzo et al 1982;van der Spoel et al 1998).…”
Section: Introductionmentioning
confidence: 99%